POLITIK HUKUM PERLINDUNGAN KOMODITAS TANAMAN PANGAN DALAM NEGERI - Eri Hendro Kusuma (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2016)
Management of natural resources in accordance with the principle of “people’s economy” that characterizes a democracy based on the values of Pancasila, has not been completely worked well. Currently 85% of all products horticulture outstanding and enjoyed by consumers in Indonesia are imported. Politics law on food in Indonesia appears to have far into the liberal economic level. This will directly impact on national food crisis. The state has a duty to achieve food sovereignty in the country. The state can carry out their vital role in suppressing or minimizing the goods imported into the territory of Indonesia for the realization of food sovereignty. http://dx.doi.org/10.17977/um019v1i12016p033